Joe Noskiyi interview 2 - Noskiyi, Joe; Crane, Ernest (Canadian Plains Research Centre, 1976)
5 p. transcript of an interview with Joe Noskiyi, conducted by Ernest Crane on an unknown date, probably between 1972-1976. Tape number IH-311A, transcript disc 40. Loss of treaty status after being accepted as treaty Indian for 40 years. Other no